Gamma Ray Irradiation Studies in Leucaena leucocephala (Lam.) De Wit. I. Effect on Germination and Seedling Height M1 - Khamankar, Y. G.; Singh, B. V. (Indian Forester, 1988)
The treated seeds were slow to germinate and the time lapse between seeding and seed emergence was found to increase with increase in radiation dose. Although pre and post-hot water treatment as well as its interaction with treatments did not show significant differences, in general the pre-hot water treatment showed comparatively greater sensitivity to radiation than post-hot water treatment both for seed germination and seedling height. Also, the insidence of lethal seedlings and sectorial chimera was more with pre-hot water treatment. Leucaena seeds showed higher radio resistance suggesting that much higher doses,than used in present investigation, can be used. The observations also point to the need for investigation on causes of high radio resistance.